Achieving green agricultural development: Analyzing the impact of agricultural non-point source pollution on food security and the regulation effect of environmental regulation - Ming Xu; Zhaoyang Lu (PLoS ONE, 2025)
Food security is the lifeline of national security. It is not only an important cornerstone for world peace, stability, and development, but also the core driving force for promoting the green development of agriculture. This paper utilizes the empirical data of 30 provinces in China from 2010 to 2022 to explore how agricultural non-point source pollution (ANSP) affects food security (FS), and also discusses the moderating effect of environmental regulations (ER). Empirical research shows that the intensification of agricultural non-point source pollution will lead to a decline in the level of food security, especially in the western areas, grain-producing areas, and grain-balanced areas. Furthermore, environmental regulations have a positive moderating effect on the impact of agricultural non-point source pollution on food security. From the perspective of the spatial spillover effect, the inhibitory effect of agricultural non-point source pollution on food security has a spillover effect in space and will radiate to the development of food security in adjacent areas. The research suggests that the local government should enhance its attention and supervision over agricultural non-point source pollution, integrate agricultural technology with environmental supervision, optimize the allocation of agricultural resources, and attach importance to the protection of the agricultural ecological environment, so as to better ensure food security and achieve green agricultural development.